2023
DOI: 10.3390/pharmaceutics15071921
|View full text |Cite
|
Sign up to set email alerts
|

Fluorinated and N-Acryloyl-Modified 3,5-Di[(E)-benzylidene]piperidin-4-one Curcuminoids for the Treatment of Pancreatic Carcinoma

Abstract: Pancreatic carcinoma is a cancer disease with high mortality. Thus, new and efficient treatments for this disease are badly needed. Curcumin has previously shown promising effects in pancreatic cancer patients; however, this natural compound suffers from inadequate efficacy and bioavailability, preventing its clinical approval. The synthetic curcuminoid EF24 was developed with activities superior to curcumin against various cancer types. In this study, a series of analogs of EF24 were investigated for anticanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 54 publications
(73 reference statements)
0
5
0
Order By: Relevance
“…In most cases, the resulting solid is separated from the reaction mixture by vacuum filtration and washed with ice water to remove the excess base. Finally, the solid product is dried and recrystallized from hexane/ethyl acetate or EtOH to obtain pure crystals [18,[23][24][25][26].…”
Section: Base-catalyzed Claisen-schmidt Condensationmentioning
confidence: 99%
See 2 more Smart Citations
“…In most cases, the resulting solid is separated from the reaction mixture by vacuum filtration and washed with ice water to remove the excess base. Finally, the solid product is dried and recrystallized from hexane/ethyl acetate or EtOH to obtain pure crystals [18,[23][24][25][26].…”
Section: Base-catalyzed Claisen-schmidt Condensationmentioning
confidence: 99%
“…Homogeneous basic catalysts allow the CSC reaction to be conducted at lower temperatures in a shorter time. Protocols based on catalysts like NaOH/EtOH [18,23,27] and NaOH/MeOH [24,[28][29][30] have been reported. Nevertheless, these methods have certain limitations, such as the following: excess or stoichiometric amounts of reactants are employed, and the reactants can be corrosive and may not be recoverable.…”
Section: Base-catalyzed Claisen-schmidt Condensationmentioning
confidence: 99%
See 1 more Smart Citation
“…In some methodologies, at the end of the reaction, the reaction mixture is neutralized by adding a hydrochloric acid (HCl) solution to the vessel [21] In most cases, the resulting solid is separated from the reaction mixture by vacuum filtration and washed with ice water, to remove excess base. Finally, the solid product is dried and recrystallized from hexane/ethyl acetate, EtOH, or EtOH/ to obtain pure crystals [16,[21][22][23][24]. Besides NaOH, calcium hydroxide (Ca(OH)2) has been used as a basic catalyst in CSC to obtain MKCs.…”
Section: Base-catalyzed Claisen-schmidt Condensationmentioning
confidence: 99%
“…Additionally, the authors found that the proapoptotic activity of compound 207 in pancreatic cancer cells surpasses the apoptosis induction properties of compound 171, and that compound 207 activates caspase-3, suppresses the antiapoptotic BCL2 and BCL-XL expression, and increase PARP cleavage in pancreatic cancer cells. They concluded that the antipancreatic cancer activity is favored by the N-acryloyl-piperidin-4-one moiety combined with 3,4-difluoro-or 3-fluoro-4-methoxy-substituted phenyl rings [22]. Curcumin A (10) inhibits human gastric cancer cells with no observable toxicity to normal cells [64].…”
Section: Anticancer Activitymentioning
confidence: 99%